A review on Comparison of Tissue Culture v/s Conventional System of Seed Potato Production - Sadawarti, Murlidhar J; Pandey, K K; Singh, S. P.; Singh, Y. P. (Indian Journal of Hill Farming, 2018)
Seed production in potato is largely being done by conventional seed production system which involves clonal multiplication by the use of potatoes. This is the transition phase of shifting whole seed production system from conventional system to hi-tech seed production system which involves micro-propagation techniques. The study of comparison of these two production system is important for researchers and seed producers. The main drawback of conventional seed production system is rapid degeneration of seed tubers by the viruses and other pathogens, low seed multiplication rate varying from 1:4 to 1:15, larger size of tubers hence high cost of seed production and time duration is more to get breeder seed. In-vitro multiplication of virus-free microplants and microtuber followed by minituber production in net house and aeroponic techniques is most important components of high-tech seed production which overcomes drawbacks of conventional seed production system. Generation-1 and Generation-2 which is supposed to be equivalent to Stage-III and Stage IV of conventional system are multiplied under field conditions as pre-breeder seed (Generation-1 and Stage-III) and breeder seed (Generation-2 and Stage IV). Comparatively hi-tech system tubers were at par with conventional system tubers with respect to growth parameters. Generation-1 (1.11%) and generation-2 (1.83%) recorded significantly lower disease percent over their respective counterpart’s stage-III (3.33%) and stage-IV (4.33%) respectively during Enzyme-linked immunosorbent assay (ELISA) testing of virus detection. Hi-tech system produces higher number of tubers than conventional system and at par total yield t/ha. The large scale multiplication with its vertical increase in half of the required time (2 years) and space, desired seed size for producing nucleus planting material along with round the year production, free from all diseases, very good quality, healthy tubers and easy to transport with very low cost confirms high-tech seed production system has an edge over conventional seed production system.